Geogebra-Assisted Problem-Based Learning and Direct Instruction Models on Mathematical Critical Thinking Based on Adversity Quotient - Nurul Rafiqah Nasution; Pradina Parameswari; Sujoko Waluyo ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
GeoGebra-assisted PBL and DI models are expected to enhance students’ mathematical critical thinking skills by providing interactive learning experiences, while AQ serves as a key factor influencing how students persist and perform in problem-solving situations. This study aims to analyze the effect of PBL and DI models, assisted by GeoGebra, on students' mathematical critical thinking based on AQ. The method employed is a quasi-experiment with a one-group pretest-posttest design and a 3×2 factorial design. Data collection was carried out through mathematical critical thinking tests, AQ questionnaires, observation sheets, and documentation. Data analysis used paired sample t-tests, and two-way ANOVA tests with the help of SPSS software. The results showed that PBL and DI assisted by GeoGebra had a significant effect on students' mathematical critical thinking, with a high influence category. PBL learning assisted by GeoGebra had a greater influence than DI assisted by GeoGebra, with an influence in the medium category. In addition, the AQ level in general did not show a significant difference in students' mathematical critical thinking, but the results of further tests showed that students with AQ Climber had higher mathematical critical thinking than AQ Camper and AQ Quitter, and AQ Camper was higher than AQ Quitter. There was no interaction effect between learning and AQ level on students' mathematical critical thinking. This finding indicates that GeoGebra-assisted PBL is more effective in students' mathematical critical thinking without being influenced by differences in AQ levels.